Productive Dowry and Women's Economic Empowerment and Their Influence on Marital Assets in Bandar Lampung - Nurnazli, Nurnazli; Pane, Erina; al Arif, M. Yasin; Akmansyah, Muhammad (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2024)
This study investigates the correlation between dowry productivity and women's economic empowerment strategies, along with their influence on marital assets. This study is significant in altering women's perceptions regarding the imperative nature of effectively managing dowry in order to enhance the economy. This study employs empirical law methodologies that are studied via the lens of reinforcement theory. Information was gathered through the use of interviews, documents, and surveys. Interviews and surveys were conducted in the city of Bandar Lampung, namely instructors at the Religious Affairs Office (KUA), and productive dowry managers, as well as prospective brides and grooms, while document analysis included journal articles, books, and legal regulations. The research findings indicate that the approach to enhancing women's economic status through the utilization of dowries commences prior to the wedding and continues until the marriage ceremony, by offering favorable incentives to women. The initial phase is dissemination, specifically emphasizing the significance of a fruitful dowry to alter women's outlook when selecting enduring dowry items. Furthermore, there is a need to enhance the availability of resources to transform dowry assets into productive assets. Thirdly, aid in the administration of the dowry procedure as a means of acquiring company capital, and fourthly, safeguarding the wife's ownership of dowry items as her personal possessions from the moment of marriage. Implementing an effective technique for enhancing dowry production will bolster the presence of marital assets. All revenues derived from the creation and administration of the dowry are the shared duty and joint property of the husband and wife. The consequences of enhancing the economic status of women through productive dowries include achieving self-reliance and resilience in the household economy.